Impact of urban spatial compactness on air pollution in China - Changyi Liang; Jing Zhao; Jing Li; Rui Zhang (Frontiers in Environmental Science)
As China’s urbanization advances, it is necessary to explore the path of reducing air pollution from the perspective of urban spatial compactness. We established a dataset containing Landcover data, PM2.5 surface annual average concentration data, urban economic statistics, and geospatial data to construct a geometric form index for Chinese prefecture level and above cities. We used OLS as well as the instrumental variable method to examine the impact of urban geometric form on air pollution from the horizontal spatial dimension, and analyzed the heterogeneity and mechanism of urban geometric form on air pollution. Our research found that compact urban geometric form significantly reduces PM2.5 concentration, indicating that the urban spatial compactness is beneficial for alleviating air pollution. A series of robustness checks and endogeneity treatment results support our benchmark conclusion. The results of heterogeneity analysis show that cities with relatively lower population density have a greater impact on reducing air pollution by adopting the compact spatial development mode. The mechanism test results indicate that the compact urban geometric form reduces air pollution by reducing traffic congestion and residents' energy consumption. However, compact geometric form may exacerbate the urban heat island effect and thus increase PM2.5 concentrations, indicating a potential negative environmental externality of urban spatial compactness. Overall, the total effect is a trade-off, with the positive environmental externalities of urban spatial compactness outweighing the negative ones.